The Study Of Men And Their Understanding About Domestic Violence In Rural Sindh, Pakistan - Buriro, Ameer Ali (2020)
This study explores and investigates men’s understanding, views, attitudes and experiences of domestic violence in rural Sindh, in Pakistan. These elements are studied by further exploring the issue of domestic violence in relation to the contexts of marriage, patriarchy and masculinity. Based on literature, these contexts greatly influence the incidents and pervasiveness of domestic violence. Methodologically, this study adopted inductive and phenomenological approaches to gather data. An Interpretative Phenomenological Analysis (IPA) method was employed to gather in-depth data that form the meaning-making and experience-sharing by the male respondents. Data is in the form a collation of narratives of male respondents from the rural areas of Sindh, Pakistan that discourses the issues of gender relations, masculinity, marriage and domestic violence from these men’s own perspectives and experiences. A total of 42 men participated in the study where face-to-face interviews were conducted with them, guided by domains of enquiries that cover concepts and elements in the research questions. A significant finding of this study is that rural men of Sindh find domestic violence as an acceptable behaviour of men and justified in many circumstances, particularly when women are seen as disobeying their husbands. In addition, the acceptance of domestic violence is closely related to the men’s views about what a man should be, based on their definitions of masculinity, and how a woman should behave, based on patriarchal norms in the society. Different forms of domestic violence are prevalent and occur in areas of study for example, physical, sexual, emotional, economic, verbal and non-verbal violence.